Nonlinear theory of elastic plates - Van, Anh Le (ISTE Press ; Elsevier, 2017)
Provides the theoretical materials necessary for the three plate models--Cosserat plates, Reissner-Mindlin plates and Kirchhoff-Love plates--in the context of finite elastic deformations. One separate chapter is devoted to the linearized theory of Kirchhoff-Love plates, which allows for the study of vibrations of a pre-stressed plate and the static buckling of a plate. All mathematical results in the tensor theory in curvilinear coordinates necessary to investigate the plate theory in finite deformations are provided, making this a self-contained resource.--Provided by publisher.